Visualization of the disordered structure of Fe-Ni Invar alloys by reverse monte carlo calculations - Kubo, Yusuke; Ishimatsu, Naoki; Kitamura, Naoto; Kawamura, Naomi; Kakizawa, Sho; Mizumaki, Masaichiro; Nomura, Ryuichi; Irifune, Tetsuo; Sumiya, Hitoshi (Frontiers in Materials, 2022)
Reverse Monte Carlo (RMC) calculation was performed to visualize the atomic arrangement in a disordered Fe$_{55}$Ni$_{45}$ alloy, which is classified as an intermediate structure between the non-crystalline glass and crystalline structures. The optimized structure of the ferromagnetic phase at low pressures revealed that Fe and Ni atoms were displaced from a perfect fcc lattice to elongate the nearest neighboring Fe-Fe atomic pairs, therefore, Fe-Fe atomic pairs have longer bond length than Fe-Ni and Ni-Ni atomic pairs. Because the elongation becomes negligible during the pressure-induced destabilization of the ferromagnetic state, the elongation of Fe-Fe pairs is the atomic scale origin of the volume expansion due to a large magnetovolume effect. Compared with the atomic arrangement in the Fe$_{65}$Ni$_{35}$ Invar alloy, a relationship between Fe-Fe atomic pairs, the Invar effect and elastic anomalies in the compression curve is elucidated.